The Global Perspectives on Sustainable Finance: Evaluating the Influence of Environmental, Social, and Governance (ESG) Criteria on Investment Portfolios - Saeed Angorani (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The goal of this study is to look at the impact of ESG criteria on the financial performance of investment portfolios. This research using a quantitative research technique, the study conducts a thorough examination of investment portfolios that incorporate ESG criteria. A sample of 500 participants was chosen to represent a varied spectrum of investors, including young, middle-aged, and older investors with varying educational, economic, and occupational backgrounds, as well as those living in urban, suburban, and rural locations. In this study, we found that there is a significant positive relationship between the adoption of ESG criteria and the financial success of investment portfolios. It also discovers that legislative frameworks have a significant influence on this connection, which may either boost or lessen the impact of ESG standards.